WEB-BASED FOOD AND BEVERAGES ORDERING INFORMATION SYSTEM AT CAFE IN BEKASI - Dewi Andryani; Devi Indriani; Risma Maulida (Asosiasi Dosen Muda Indonesia, 2023)
A cafe is a place that serves food and drink orders in a relaxed or informal atmosphere, a cafe is also a center for social interaction where people can gather to read, write, have business meetings, or just fill their spare time. Recording of food and beverage orders at the Freezing Point Cafe is still done manually and the sales system is still offline where if a buyer wants to order food from the cafe they have to come to the location so it is time consuming and inefficient and many people don't know about the cafe, so a This web-based Food & Beverage Ordering Information System aims to introduce the Cafe to the wider community and make it easier for buyers to place orders for food and drinks offered by the CafÃ© without coming directly to the location. This study uses the SDLC method which consists of Planning, Analysis, Design, Implementation and Testing. The results of the tests that have been carried out can be concluded that this website has been successfully created, which in terms of appearance is quite attractive, all the menus on the website function properly and are in accordance with the designs and algorithms that have been made before.